READER'S MOTIVATION AND BEHAVIOR TOWARD LECTURER'S DECISION IN CONSUMING MEDIA - Ariani, Annestie; Sarma, Ma'mun; Najib, Mukhamad (Universitas Brawijaya, Indonesia, 2017)
Today print media face serious problem. Technology advances in communication and information sector has caused online media grow rapidly replacing the function of print media. The growth of online media caused some print media industries change their product into the online version, even some of them stop producing. This study aims to see the influence of online media towards the consumption of print media from the consumers'point of view. This study was conducted in Institut Pertanian Bogor with 92 lecturers as respondents. Proportional random sampling technique was used in this study. Structural Equation Model based on SMART Partial Least Square v2.0 with four latent variables which were reader's motivation, behavior of reading print media, behavior of reading online media, and media consumption decision were used in this study to analyze the data. The result of the analysis showed that (1) reader's motivation directly had significant effect on reader's consumption decision, (2)reader's motivation directly had significant effect on behavior of reading print media, (3 )reader's motivation had significant effect on behavior of reading online media, and (4) behavior of reading print media had insignificant effect on the media consumption decision (5) behavior of reading online media had insignificant effect on the media consumption decision.